(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
This article explores strategies aimed at improving the oral speech competence of students. Effective oral communication skills are essential for academic success, professional development, and interpersonal interactions. Through a review of current research and best practices, this study examines various approaches to enhancing students’ oral speech competence, including speech training programs, classroom activities, and technology integration. The article also discusses the importance of teacher training, peer collaboration, and feedback mechanisms in facilitating skill development. By implementing targeted interventions and fostering a supportive learning environment, educators can empower students to become confident and articulate communicators